Design of a Wideband RF Front-End Architecture for Advanced 6G Transceiver Systems - Ishrat Z. Mukti; Ebadur R. Khan (Electronics, Communications, and Computing Summit, 2025)
It is an article on the implementation of a re-configurable RF front-end system that is the modern wideband energy-efficient system. The 6G paradigm can potentially have a very wide frequency range of operation that includes the sub-terahertz as well as millimeter-wave bands; therefore, the proposed design achieves some of the most significant requirements of the 6G paradigm that is defined as high bandwidth, low noise figure, and high linearity. This architecture contains a broadband inductive source-degenerated low-noise amplifier (LNA) and better gain flatness, a double-balanced Gilbert-cell mixer with high linearity and effective conversion gain and a Doherty based power amplifier (PA) that achieves the maximum power efficiency in the mmWave band. It also has programmable filters, and RF switches such that, spectrum agility can be obtained on dynamic accompaniments of several working bands. To allow an adaptive and multiband operation the front-end is reconfigurable using passive elements and other variable filter designs, and operates in CMOS-SiGe BiCMOS technology. Keysight ADS and Cadence simulation tools were applied in the simulation of the circuit level performance of the given architecture. The experimental observations show that front-ends gain greater than 20 dB, noise figure less than 3 dB and input third-order intercept point (IIP3) more than 10 dBm at 0.1-0.3 THz. Moreover, the architecture can perform dynamic frequency tuning with low power overhead and hence, multi-standard charts of beamformed 6G transceivers are very convenient. The paper provides scalable and versatile RF front end design capable of meeting the high data rates, flexible spectrum and low energy consumption needs in the future wireless communication system.